2021
DOI: 10.3390/app11020813
|View full text |Cite
|
Sign up to set email alerts
|

Concrete Crack Detection Based on Well-Known Feature Extractor Model and the YOLO_v2 Network

Abstract: This paper compares the crack detection performance (in terms of precision and computational cost) of the YOLO_v2 using 11 feature extractors, which provides a base for realizing fast and accurate crack detection on concrete structures. Cracks on concrete structures are an important indicator for assessing their durability and safety, and real-time crack detection is an essential task in structural maintenance. The object detection algorithm, especially the YOLO series network, has significant potential in cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…As for the feature extraction layer, the last CONV of the pretrained CNN model was selected based on empirical analysis. The design of network layer was primarily based on the official manuals of the MATLAB and our previous research results (Teng et al 2021;Lin et al 2022). The previous work has explained the functions of all layers in detail and confirmed that these layers have excellent performance for defect image detection.…”
Section: Faster R-cnnmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the feature extraction layer, the last CONV of the pretrained CNN model was selected based on empirical analysis. The design of network layer was primarily based on the official manuals of the MATLAB and our previous research results (Teng et al 2021;Lin et al 2022). The previous work has explained the functions of all layers in detail and confirmed that these layers have excellent performance for defect image detection.…”
Section: Faster R-cnnmentioning
confidence: 99%
“…It is difficult to evaluate the detection effects based on P and R individually as they are lack of overall information. Instead, AP is a comprehensive indicator of P and R and is thus commonly used to evaluate the network performance (Maeda et al 2018;Deng et al 2020;Zhang et al 2020;Teng et al 2021). The value range of AP is 0-1, the closer the AP value to 1, the more excellent is the detection effect.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Visual inspection datasets are small scale and are expensive to curate. Therefore, several studies adopt standard architectures-such as VGG16, Inception-v3, LeNet, YOLO, or ResNet50 often pre-trained with IMAGENET representations-for the detection of cracks [31,56,61,75], potholes [39], spalls [68], and multiple other damages including corrosion, seapage, and exposed bars [17,28,72,78]. In Table 1, we provide a non-exhaustive list of recent literature studies that have used transfer learning for concrete damage detection tasks.…”
Section: Damage Detection Using Deep (Transfer) Learningmentioning
confidence: 99%
“…Zheng et al [ 24 ] proposed a convolution neural network based on YOLOv3 to detect bearing-cover defects. Teng et al [ 25 ] used a well-known feature extractor model and the YOLOv2 network to detect a concrete crack. Li et al [ 26 ] proposed an enhanced YOLOv3 tiny network for real-time ship detection.…”
Section: Introductionmentioning
confidence: 99%